102k views
3 votes
-6 (w - 4 ) + 8w = 2 (w + 9)

1 Answer

2 votes

Answer:


w=0

Explanation:

First, we resolve the multiplication using the distributive property. We multiply -6 by each factor on the parenthesis.


-6w +24+ 8w = 2w+18

We add -6w and 8w.


2w+24 = 2w+18

Every term that contains a w goes to the left,and the ones that don't have it, to the right. Remember to change the signs!


2w-2w= 18-24

We add and substract:


0w= -6

We send the zero that is multiplying the W, to the right divding -6.


w= -6:0


w=0

User Jonycheung
by
5.4k points